Adiabatically prepared spin-lock approach for T1ρ-based dynamic glucose enhanced MRI at ultrahigh fields - Schünke, Patrick; Mundiyanapurath, Sibu; Radbruch, Alexander (Magnetic resonance in medicine, 2017)
Chemical exchange sensitive spin-lock and related techniques allow to observe the uptake of administered D-glucose in vivo. The exchange-weighting increases with the magnetic field strength, but inhomogeneities in the radiofrequency (RF) field at ultrahigh field whole-body scanners lead to artifacts in conventional spin-lock experiments. Thus, our aim was the development of an adiabatically prepared T1ρ-based imaging sequence applicable to studies of glucose metabolism in tumor patients at ultrahigh field strengths.
Published online: 13 August 2016
Gesehen am 23.06.2017